Role of Dapagliflozin and Liraglutide on Diabetes-Induced Cardiomyopathy in Rats: Implication of Oxidative Stress, Inflammation, and Apoptosis - El-Shafey, Mohamed; El-Agawy, Mosaab Salah El-din; Eldosoky, Mohamed; Ebrahim, Hasnaa Ali; Elsherbini, Dalia Mahmoud Abdelmonem; El-Sherbiny, Mohamed; Asseri, Saad Mohamed; Elsherbiny, Nehal M. (Frontiers in Endocrinology, 2022)
The current study aims to assess protective effects of dapagliflozin (a sodium glucose cotransporter-2 inhibitor, Dapa) and/or liraglutide (a glucagon-like peptide 1 agonist, Lira) in experimental model of diabetic cardiomyopathy (DCM). Single dose of streptozotocin (STZ) was administrated to male Sprague Dawley rats by intraperitoneal injection at a dose of 50 mg/kg to induce diabetes mellitus. Dapa (1 mg/kg, orally), Lira (0.4 mg/kg, s.c.) and Dapa-Lira combination were administrated for 8 weeks once-daily. Blood samples were evaluated for glucose level and biochemical markers of cardiac functions. Cardiac tissue were dissected and assessed for redox homeostasis (MDA, GSH and CAT), pro-inflammatory mediators (NF-κB, TNF-α) and apoptotic effectors (Caspase-3). Moreover, effect of treatments on cardiac cellular structure was studied. Dapa and/or Lira administration resulted in significant improvement of biochemical indices of cardiac function. Additionally, all treatment groups demonstrated restoration of oxidant/antioxidant balance. Moreover, inflammation and apoptosis key elements were markedly down-regulated in cardiac tissue. Also, histological studies demonstrated attenuation of diabetes-induced cardiac tissue injury. Interestingly, Dapa-Lira combination treatment produced more favourable protective effect compared to single treatment. These data demonstrated that Dapa, Lira and their combination therapy could useful in protection against DM-accompanied cardiac tissue injury, shedding the light on their possible utilization as adjuvant therapy for management of DM patients